Single cell RNA sequencing research in maternal fetal interface - Chen, Qian; Shan, Dan; Xie, Yupei; Luo, Xingrong; Wu, Yuxia; Chen, Qiuhe; Dong, Ruihong; Hu, Yayi (Frontiers in Cell and Developmental Biology, 2023)
The maternal-fetal interface is an essential environment for embryonic growth and development, and a successful pregnancy depends on the dynamic balance of the microenvironment at the maternal-fetal interface. Single-cell sequencing, which unlike bulk sequencing that provides averaged data, is a robust method for interpreting the cellular and molecular landscape at single-cell resolution. With the support of single-cell sequencing, the issue of maternal-fetal interface heterogeneity during pregnancy has been more deeply elaborated and understood, which is important for a deeper understanding of physiological and pathological pregnancy. In this paper, we analyze the recent studies of single-cell transcriptomics in the maternal-fetal interface, and provide new directions for understanding and treating various pathological pregnancies.